Alternatif Pengembangan Industri Kreatif Islami Melalui Penguatan Human Capital di Indonesia - Muhammad As'ari Hasan (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
Human Capital is an important point in an industry, the urgency of human Capital is the main ecosystem which is the government's priority in realizing the creative industry. The index of increasing human development has increased not so significantly. Even though human capital can accelerate the growth of creative industries, especially sharia creative industries. The sharia industry is an alternative to developing a creative economy based on sharia principles. the potential for sharia creative industries in Indonesia is quite large and continues to grow. The sharia creative products developed by these industry players have high added value and have a wide market, both at home and abroad. The implications for the development of sharia creative industries for the development of the creative economy as a whole are also quite large. The development of sharia creative industries can improve the quality of products and services produced, and can open wider and more sustainable employment opportunities. In addition, sharia creative industries can also help promote sustainable economic growth and generate wider social benefits for society. the development of sharia creative industries is an alternative to the development of a very potential creative economy in Indonesia. The development of sharia creative industries can provide broader economic and social benefits, and can help promote sustainable and inclusive economic growth.